PENGEMBANGAN MODUL AJAR BERBASIS ANDROID UNTUK SISWA SMK - Mujiono, Franciscus; Ismawati, Esti; Hersulastuti, Hersulastuti (Steam Engineering, 2024)
This study aims to describe and analyze the feasibility, practicality and effectiveness of Android-based Indonesian language and literature teaching modules for grade XI vocational high school students. This study uses the Research and Development (R&D) method referring to the ADDIE model steps developed by Dick and Carey which include needs analysis, e-module design, e-module development, implementation, and evaluation. The subjects of the study included 1 media expert, 1 learning design expert and 1 subject matter expert, and 35 grade XI students of SMK Leonardo Klaten. The instruments used to assess the feasibility of this e-module include a feasibility assessment sheet by media experts, a feasibility assessment sheet by learning design experts and subject matter experts and a student response questionnaire on the use of the e-module. The results of the study showed that the Android-based Indonesian language and literature teaching material e-module was declared very valid with an average overall score of 96% for media experts, learning design experts with an average score of 92% and subject matter experts with an average score of 93%. The results of student responses as users obtained an average value of 4.70 with a percentage of results of 94.1% so that the developed e-module is included in the category of "Very practical". In the analysis of student learning outcomes data, the N Gain result was 0.57, so the e-module was interpreted as a moderate category. The interpretation category of N-Gain effectiveness is quite effective